Strategi Pemerintah Desa dalam Mewujudkan Prinsip Efektivitas Pada Pelayanan Pembuatan E-KTP di Desa Sukodono Kecamatan Dampit Kabupaten Malang - Nindi Karindra; Agus Satmoko Adi (Universitas Negeri Surabaya (Unesa), 2023)
Public service is one form of the State's efforts to fulfill the basic needs of every citizen. So that the effectiveness of a government system plays an important role in measuring the success of a service. The purpose of this study was to determine the strategy adopted by the village government in realizing the principle of effectiveness in the service of making Electronic Identity Cards (e-KTP) in Sukodono Village, Dampit District, Malang Regency. In order to achieve this goal, this research uses a qualitative research type with descriptive method. The data collection technique was through observation and interviews with the Sukodono Village Head and several village officials as supporting informants. The results obtained in the study show several strategies carried out by the village government to realize the principle of effectiveness in the service of making e-KTP in Sukodono Village such as strengthening the vision and mission, providing incentives to the apparatus, increasing accountability, determining organizational structure, and changing the performance of the apparatus. . This strategy is considered effective as an effort of the Sukodono village government in realizing the principle of effectiveness, especially in the service of making e-KTP in Sukodono Village, Dampit District, Malang Regency. Keywords: strategy, government, effectiveness.